Employee empowerment, career satisfaction and intention to stay of employees in a printing organisation in Pretoria - Mqokozo, Adelaide Zandile (Vaal University of Technology, 2022)
This study aimed at investigating a relationship between employee empowerment, career satisfaction and intention to stay of employees in a printing organisation in Pretoria, South Africa. One of the crucial tasks of government is to build a public service that is capable of meeting the needs of South African citizens. Government will not be able to improve public service delivery without working together with the public servants, who are the major role-players in ensuring that the above is achieved successfully. The study was intended to investigate the relationship between employee empowerment and career satisfaction with a view to retain the employees of the Government Printing Works. This study followed a quantitative research approach, and a structured questionnaire was used to collect data on the constructs. The questionnaire consisted of four sections. Section A solicited information on participants’ demographic profile. Section B contained questions on Employee empowerment, Section C on career satisfaction and Section D on intention to stay. The results of the correlation analysis in this study revealed that there is a significant moderate positive relationship between employee empowerment and career satisfaction. The results also revealed a weak positive relationship between employee empowerment and intention to stay. Based on the findings, a number of recommendations were made to help improve employee empowerment, career satisfaction and increase the intention to stay of employees. It was therefore recommended that conditions which may lead to employees feeling powerless should be identified and removed and certain powers should be delegated to employees to enable work decisions to be taken quicker and encourage innovativeness of employees. Since the study results highlighted an existence of a strong relationship between career satisfaction and intention to stay, it is necessary to increase career satisfaction in order to increase intention to stay. In order to improve career satisfaction among employees, it was therefore recommended that Government Printing Works should avail opportunities for growth and more responsibility for employees by providing them with jobs that will not only challenge them but give them a sense of reward and fulfilment at the same time. The study contributes to the body of knowledge by providing increased understanding of employee empowerment, career satisfaction and intention to stay of employees in the government sector, specifically in the unexplored territory of government printing. The study also suggests future research opportunities on its constructs, specifically in the printing and public sectors. It is recommended that future research incorporate more than one organisation in the printing sector and more than one government department. Since this study made use of a quantitative research design, future research on these constructs could take on a qualitative or mixed methods approach to gain a deeper understanding of the constructs and their relationships.
MM (HRM) (Department of Human Resource Management, Faculty of Management Sciences), Vaal University of Technology.
Keywords: Employee empowerment; Career satisfaction; Intention to stay; Printing; Organisation; Government; Employees; Dissertations, Academic -- South Africa.; Employee empowerment.; Employee motivation.; Job satisfaction.